Influence of environmental factors on bird diversity in and around Kahundanda Hillscape, Pokhara, Nepal - Bastola, Shubhas Chandra; Adhikari, Jagan Nath; Dhakal, Hemanta; Bhattarai, Bishnu Prasad (Nepalese Journal of Zoology, 2022)
Birds are the indicators of ecosystem health. Several environment variables affect the diversity, distribution and migration of birds. Kahundanda of Pokhara Valley is one of the important hillscapes having different habitat types such as human settlements, forest, farmland, wetland and open areas. This study revealed the factors affecting the diversity and distribution of birds of Kahundanda. The direct observation by “point count” method was applied for the bird survey. A total of 49 points were fixed along the nine transects in every 200–250m distance of the Kahundanda (elevation ranges from 700m to 1424m). In each point, we also recorded habitat types and disturbance factors. A total of 101 species of birds belonging to 18 orders and 41 families were reported from the study area. The species diversity was the highest in forest habitat (H' = 3.558) and least in open area (H' = 2.365). Among them, 58.42% of birds were resident and 41.58% were migratory including four globally threatened (one critically endangered, two endangered and one near threatened) species. Other factors such as the number of livestock present, distance from roads and settlement, environmental factors such as distance from the water resources, elevation and number of fruiting trees present significantly affected the distribution of the birds at Kahundanda. Thus, environmental factors such as habitat types, human disturbance and proximity to water resources are important for bird species conservation in the human-dominated landscape.